"We're open to all": The paradox of diversity in the U.S.-based free fitness movement. Issue 2 (15th March 2023) - Carter, Andrew; Alexander, Adam C.; Gomez, Vicky; Zhang, Ni; Allen, Monica
ABSTRACT: Recent interdisciplinary scholarship has drawn increased critical attention to issues related to race, gender, class, and culture within public physical activity (PA) spaces, foregrounding the importance of rethinking dominant narratives of PA and promoting diverse and more inclusive practices within these contexts to address PA disparities. This paper addresses issues related to diversity and inclusion within community fitness spaces by examining the experiences of stakeholders and members involved in 'The Collective' Free Fitness Group (CFFG), a free, open-to-the-public fitness community based in Oakland, Ca (the original name has been changed for purposes of anonymity). This organization has made intentional efforts towards addressing diversity and inclusion across its membership and is located in one of the most ethnoracially diverse regions of the country. Drawing on McGee's (1980) concept of ideographs, we explore the potential limitations and consequences of how the CFFG Oakland community members communicated discourses and lived experiences of and to one another and the broader Oakland community. Specifically, we argue that by emphasizing certain expressions of and while deemphasizing alternative forms, participant responses reflected a 'paradox' of diversity, despite their shared in-group identification around as an important individual moral virtue and their open and community. This study contributes new knowledge to the 'paradox' literature and may inform future physical activity interventions and theoretical directions of study.